The Relationship between Income Distribution, Inflation and Economic Growth: Examining the Asymmetric Relationship Based on the Kuznets Hypothesis with Fourier Functions - Serhat Alpağut (Ekonomi, Politika & Finans Araştırmaları Dergisi)
The relationship between inflation, economic growth, and income distribution in Türkiye is examined in this study. The F-ADL cointegration test was applied as the econometric method. The first result obtained is that economic growth has an increasing effect on income inequality. The second result is that inflation has a reducing effect on income inequality. The third result is that inflation and economic growth have an asymmetric relationship with income distribution. Economic growth initially has a positive effect on income inequality and then a negative effect beyond a certain threshold, indicating a “reverse U” shaped relationship. This result shows that the Kuznets hypothesis is valid in Türkiye. Regarding the relationship between inflation and income inequality, inflation initially has a negative effect, and then, after a certain threshold, the effect becomes positive, indicating a “U” shaped relationship. The findings are consistent with the literature. When relationships are linear, a single policy may be sufficient; however, in cases of asymmetric relationships, varied and multiple policies may be required. Thus, it is advisable to consider the asymmetry in the design of income distribution-regulating and welfare-enhancing economic policies.